Isolation, Purification, Identification and Binding Site Analysis of Walnut Glutelin Peptides and Their Zinc Chelates - MEI Jie, LI Fang, WANG Xiaowen, MA Hui, QIU Xiaorou, LIU Siyue, KONG Lingming (Shipin Kexue)
In order to improve the added value of walnut, walnut glutelin peptides (WGPs), which were prepared from walnut meal, were chelated with zinc ions. The zinc chelating characteristics of WGPs were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD) spectroscopy. The peptides were screened for zinc binding capacity by ultrafiltration, gel column chromatography and liquid chromatography-tandem mass spectrometry (LC-MS/MS), and the specific binding sites and binding capacity of the peptides were explored by molecular docking. The results showed that WGPs could chelate with zinc ions, leading to significant alterations in the surface microstructure and crystallinity of the peptides. After ultrafiltration and gel column chromatography, fraction F41, which had the highest chelating capacity of (117.43 ± 1.99) mg/g, was obtained. By LC-MS/MS combined with virtual screening, five potential bioactive peptides without toxicity or allergenic potential were identified. Molecular docking was used to simulate and analyze the binding process. It was found that pentapeptide Phe-Asp-Ala-Asp-Phe (FDADF) could form a structurally stable complex with zinc ions through coordination bonds, hydrogen bonds and hydrophobic interactions. Among the five peptides, the pentapeptide exhibited the lowest binding energy (−7.27 kcal/mol), and the main binding site was the carboxyl oxygen atom (Asp4:O-Zn) of the aspartic acid (Asp) side chain. This study provides a theoretical basis for the development and application of zinc-chelating peptides.